Spatial processing is frequency-specific in auditory cortex but not in the midbrain - Sollini, Joseph A.; Mill, Robert; Sumner, Christian J. (Society for Neuroscience, 2017)
The cochlea behaves like a bank of band-pass filters, segregating information into different frequency channels. Some aspects of perception reflect processing within individual channels, but others involve the integration of information across them. One instance of this is sound localization, which improves with increasing bandwidth. The processing of binaural cues for sound location has been extensively studied. However, while the advantage conferred by bandwidth is clear we currently know little about how this additional information is combined to form our percept of space. We investigated the ability of cells in the auditory system of guinea pigs to compare interaural level differences (ILDs), a key localization cue, between tones of disparate frequencies in each ear. Cells in auditory cortex, believed to be integral to ILD processing (Excitatory from one ear, Inhibitory from the other: EI cells), separately compare ILDs over restricted frequency ranges, not consistent with their monaural tuning. In contrast, cortical EE (Excitatory from both ears) cells showed no evidence of frequency-specific processing. Both cell types are explained by a model in which ILDs are computed within separate frequency channels and subsequently combined in a single cortical cell. Interestingly, ILD processing in all inferior colliculus cell types (EE and EI) is largely consistent with processing within single matched frequency channels from each ear. Our data suggests a clear constraint on the way that localisation cues are integrated: cortical ILD tuning to broadband sounds is a composite of separate frequency-specific binaurally sensitive channels. This frequency-specific processing appears after the midbrain.